Integrating Prophetic Justice and Maqāṣid al-Sharī‘ah In Administrative Resolution of Electoral Process Disputes In Indonesia - Mawardi, Irvan; Utama, Yos Johan; Wisnaeni, Fifiana (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This article examines the structural limitations in the administrative mechanism for the resolution of electoral disputes (SPPU) in Indonesia and analyzes how these weaknesses impact the protection of citizens' voting rights and the integrity of democracy. The main issues to be studied are structural and procedural weaknesses in the resolution of electoral disputes, the value of prophetic justice, and an integrative adjudication model that can strengthen substantive justice in the resolution of election disputes at the State Administrative Court (PTUN). Using a socio-legal approach combined with the theory of maqāṣid al-sharī‘ah, this study examines the regulatory framework, judicial practices, and principles of Islamic law particularly humanization, liberation, transcendence, maṣlaḥah, izālat al-ḍarar, and raf‘al-ḥaraj. The research findings show that prophetic values ​​provide an ethical foundation for the State Administrative Court (PTUN) to orientate itself toward protecting public rights, while maqāṣid al-sharī‘ah provides a teleological framework that allows judges to interpret procedural boundaries more proportionately to achieve substantive justice. This article proposes a prophetic–maqāṣid adjudication model that encompasses expanding legal standing for voters, testing administrative actions in the form of omissions, flexible deadlines, adaptive standards of proof, and ethical guidelines for judges' deliberations. This integrative model strengthens the PTUN's role as a guardian of electoral justice while harmonizing Islamic moral values ​​with constitutional democratic governance.